STUDENTS' ANXIETY IN SPEAKING ENGLISH - Indrianty, Septy (2012)
The study investigated students' anxiety in speaking English in one Hotel and Tourism College in Bandung. This study examined types of anxiety, sources of anxiety and the strategies to reduce anxiety. This study employed a qualitative research design, implementing characteristic of a case study. The data were obtained through observation of class interactions and interviews. The data from classroom observations and interviews were, then, analyzed descriptively and interpreted to answer the research questions. The study revealed three findings related to research questions. First, two types of anxiety were evidenced, i.e. trait anxiety and state/situational anxiety. Second, the students' anxiety in speaking English was derived from three main sources of anxiety, i.e. communication apprehension, test anxiety and fear of negative evaluation. Moreover, as the interview data revealed, lack of vocabularies and lack of preparation have also contributed to students' anxiety in speaking. Third, the students employed some strategies to reduce anxiety, namely using mime/gesture, appealing for help and code switching. These findings suggest that the teacher should be more aware of students' anxiety in order to arouse students' motivation to speak up confidently and fluently in an English speaking class. As such, teachers are urged to be fairly creative in devising better techniques that could encourage the students to speak more. Finally, teachers should also provide materials which contribute to students' vocabularies and confidence, so that the students have abetter performance in speaking English in the future.